COMPARISON OF Manihot utilisima (PATI UBI WOOD) ADDITION TO DIMENSIONAL STABILITY OF IRREVERSIBLE HYDROCOLLOID MOLD - Ilmianti; Muhammad Iqbal; Muhammad Hidayatullah (Journal of Health and Dental Sciences, 2021)
Alginate impression material is used to print the teeth and the oral tissues; alginate molding material is from abroad and expensive. Modification to the impression material alginate with cassava starch with 1: 1 obtained detailed reproduction of the same printed material alginate without added with cassava starch. The study's objective was to get an alternative form of printed material alginate plus Manihot utilisima (cassava starch) with the nature of the physical properties following the standard. The study methods used laboratory experiments. The materials used in this study were printed material alginate (Hydrogum fast setting), starch cassava starch cap dua kelinci, water, and tools calliper inside digital. There were four groups of a control group, a group cassava starch ratio of 50: 50, groups of cassava starch ratio of 60: 40, and a comparison group of cassava starch 70: 30. The results were dimensional stability of printed materials Alginate without additions were (73.72, 48.77, 30.51), the dimensional stability of the printed material alginate with a ratio of 50: 50 were (74.24, 40.82, 30.76), the dimensional stability of the printed material alginate with a ratio of 60: 30 were ( 75.39, 49.67, 31.57), and the results of dimensional stability alginate ((irrevesible hydrocolloid ) molding material with a ratio of 70: 30 were (76.36, 50.94, 32.86). The conclusion is the addition of Manihot utilisima on standard printed material alginate (irrevesible hydrocolloid) obtained dimensional stability test results that met the standards at a ratio of 50: 50 of ANSI/ADA no.18/1992. Manihot utilisima was one of the appropriate alternatives as a mixture in impression material alginate (irrevesible hydrocolloid). DOI : 10.54052/jhds.v1n1.p19-26